Performance Evaluation of Log-normal And Negative Exponential Channel Modeling Using Various Modulation Techniques in OFDM-FSO Communication - Singh, Nitin Shankar; Singh, Gurpartap (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Free Space Optics (FSO) is one of the emerging technology which is thoroughly being popular and is basically using optical signals for the communication. The paper evaluates the bit error rate performance of the Free space Optics (FSO) system. To design a high performance communication link for the atmospheric FSO channel, it is of great importance to characterize the channel with proper model. The performance of the highly efficient, high data rate system is limited by the certain constraints like scintillation effects and atmospheric turbulence. The FSO communication system using Orthogonal Frequency Division Multiplexing (OFDM) technique which is known for its increased robustness against frequency selective fading, narrow-band interference and high channel efficiency. The performance of the modulation techniques- Binary Phase Shift Keying (BPSK), Quadrature Phase Shift Keying (QPSK) and 8-PSK are studied in the Lognormal and Negative Exponential channel. The obtained results are the comparative study of Bit Error Rate (BER) vs. Signal to Noise Ratio (SNR), which is quite useful for analyse the system performance with different channel models for various modulation techniques.